Confronting myths: agricultural citizenship and temporary foreign worker programs. (14th May 2019) - Venkatesh, Vasanthi
This paper provides a conceptual intervention through an analysis of the myths surrounding agricultural citizenship and migrant work that underlie the temporary foreign worker program in two settler countries: Canada and Israel. The paper offers a brief insight into the ideologies around farm work that informed the colonisation and dispossession of Indigenous peoples and the expropriation of non-citizen labour. It begins with a historical overview of how agriculture was used as a tool of colonisation even as settlers struggled to cultivate Canadian lands because of the seasonal nature and the persistent lack of labour. From the time of Confederation, agriculture began to be intimately tied with immigration policies culminating in the Seasonal Agricultural Worker Program (SAWP) that persists to this day. The paper then expands the analysis to Israel to show how other settler nations have also followed similar ideological and policy trajectories. The paper illustrates how racial capitalism intertwines with settler colonial practices discursively and institutionally through immigration policies.